Finding your way with your baby : the emotional life of parents and babies - Daws, Dilys; De Rementeria, Alexandra (London : Routledge, 2021)
Finding Your Way with Your Baby explores the emotional experience of the baby in the first year and that of the mother, father and other significant adults. This updated edition is informed by latest research in neuroscience, psychoanalysis andinfant observation and decades of clinical experience. It also includes important new findings about how the mother's brain undergoes massive restructuring during the transition to parenthood, a phenomenon that has been named matrescence.' The authors engage with the difficult emotional experiences that are often glossed over in parenting books - such as bonding, ambivalence about the baby, depression and the emotional turmoil of being a new parent. Acknowledgement and understanding of this darker side of family life offer a sense of relief that can allow parents to harness the power of knowing, owning and sharing feelings to transform situations and break negative cycles and old ways of relating. With real-life examples, the book remains a helpful resource for parents, as well as professionals interested in ideas from psychoanalytic clinical practice including health visitors, midwives, social workers, general practitioners, paediatricians and childcare workers.
A note rom Dilys Daws; A note on the authors; Acknowledgemets; Introduction; PART I: Becoming a parent 1. Life will never be the same again; 2 Bringing your baby home; 3. Bonding; 4. Being a good parent; 5. Figuring out fatherhood; 6. Baby blues, postnatal depression and anxiety; PART II: Being with baby; 7. Conversations with your baby; 8. Feeding; 9. Sleeping; 10. Crying babies; 11. Weaning and teething; 12. Learning through play; 13. Your baby's emerging sense of self; PART III: The wider world; 14 Wider family and other support; To work or not to work; Recommended Readings; References; Index
Keywords: Parent and infant; Parenthood -- Psychological aspects; Emotions; PSYCHOLOGY / Developmental / Child; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Mental Health